Energy and resource recovery through integrated sustainable waste management. (1st March 2020) - Moustakas, K.; Rehan, M.; Loizidou, M.; Nizami, A.S.; Naqvi, M.
Abstract: This editorial is prepared for the Applied Energy Journal as a Virtual Special Issue (VSI) and it overviews the research work presented at the NAXOS 2018 6th International Conference on Sustainable Solid Waste Management, held from 13th to 16th June 2018 in Naxos Island, Greece. The research articles presented in VSI highlight the recent developments in waste valorisation for the recovery of energy, fuels and value-added products. They also cover the primary hurdles and potential solutions moving towards more sustainable society. This editorial not only presents the overall summary of the extended research papers from NAXOS 2018, but also provides an overview of the current trends and developments in the fields of waste management, waste valorization, and energy production systems. The articles published in this VSI cover a wide range of topics, including energy recovery from waste, waste to energy technologies, sustainable energy systems, anaerobic digestion, thermal arc plasma gasification, microalgal-based biorefinery, waste management, modelling of advanced gasification systems, waste valorization, and microbial fuel cell technology. 10 manuscripts, out of total 21 extended mansucripts invited, were accepted for publication in the Applied Energy Journal through peer review process conducted by the expert reviewers in the relevant fields with the aid of the guest editors.